2003
DOI: 10.1590/s0074-02762003000700015
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of adhesion moleculesshaping the T-cell subset prevalence during the early phase of autoimmune and Trypanosoma cruzi-elicited myocarditis

Abstract: The participation of cell adhesion molecules (CAMs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Moreover, ICAM-1 ϩ and VCAM-1 ϩ blood vessels were associated with the presence of CD8 ϩ -infiltrating T cells in the cardiac tissue of chagasic patients with severe cardiomyopathy (38). In addition, cardiomyocytes express ICAM-1 during the acute phase of experimental T. cruzi infection (27,30). Considering that ICAM-1-mediated interactions plays a crucial role in forming the immunological synapse (29,39), ICAM-1 ϩ myocytes could be targets for LFA-1 ϩ cytotoxic T cells, contributing to heart dysfunction during chagasic myocarditis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, ICAM-1 ϩ and VCAM-1 ϩ blood vessels were associated with the presence of CD8 ϩ -infiltrating T cells in the cardiac tissue of chagasic patients with severe cardiomyopathy (38). In addition, cardiomyocytes express ICAM-1 during the acute phase of experimental T. cruzi infection (27,30). Considering that ICAM-1-mediated interactions plays a crucial role in forming the immunological synapse (29,39), ICAM-1 ϩ myocytes could be targets for LFA-1 ϩ cytotoxic T cells, contributing to heart dysfunction during chagasic myocarditis.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the induction and up-regulation of expression of VCAM-1, a VLA-4 ligand (28), and ICAM-1, a LFA-1 ligand (28), on cardiac vascular endothelium were associated with the establishment of the early acute T. cruzi-elicited myocarditis (27). Moreover, ICAM-1 ϩ and VCAM-1 ϩ blood vessels were associated with the presence of CD8 ϩ -infiltrating T cells in the cardiac tissue of chagasic patients with severe cardiomyopathy (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockade of one, CCR5, by Met-RANTES significantly decreased the intensity of cardiac inflammatory infiltrate, suggesting that lymphocyte migration to the myocardium during acute infection is dependent on CCR5 ligands [42,43] . IFN-γ-inducible adhesion molecules, such as fibronectin and VCAM-1, can also be detected at high levels in cardiac tissue from T. cruzi-infected mice [44] . Few studies have investigated the immunology of the acute phase infection in human patients.…”
Section: Ifn-γ Acts As An Immunological Mediator Inducing Protection mentioning
confidence: 99%
“…Studying C3H/He mice chronically infected with the Colombiana strain of T. cruzi we showed the prevalence of CD8 + T cells in the inflamed heart (dos Santos et al 2001). Further, recently we have shown that the establishment of the CD8 + T cells predominance in the cardiac tissue of T. cruziinfected mice is a rather precocious process, being detected during the early acute phase (Marino et al 2003a). Trying to understand the molecular mechanisms involved in T. cruzi-elicited myocarditis with prevalence of CD8 + T cells, we have investigated the expression of inflammatory CC-chemokines in the heart of Colombiana straininfected C3H/He mice.…”
mentioning
confidence: 97%